Penyesuaian Kebijakan Perjanjian Internasional Indonesia Untuk Mencapai Target Emisi Dalam Kerangka Perjanjian Paris - Nasriel Ikhsan; Qaulan Sadidah; Salsabilah Putri Maesa Daulay (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This article discusses how the process of adapting the Paris Agreement from international law to Indonesian national law, the process of Indonesia entering into an international agreement through the Paris Agreement and also what are the challenges and impacts of ratifying the Paris Agreement into Indonesian national law. By using a normative approach used to assess ideal policies, it was found that Indonesia has ratified the Paris Agreement through Law No. 16 of 2016 to address climate change and achieve emission targets. This ratification brings various challenges and impacts, but also improves Indonesia's national legal standards. This step demonstrates Indonesia's serious commitment to international agreements and reflects ongoing efforts in planning and implementing climate policies with a five-year medium-term target, from these results the author recommends, the author's advice is that Indonesia must be more realistic in seeing the conditions that occur in the field in implementing its commitments to the Paris Agreement, which means that the launch of commitments must be based on plans that can be implemented to avoid failure in the implementation. And Indonesia must firmly carry out its commitments, one of which is through existing policies, policies made must be based on loyal commitments and implemented firmly and bindingly. Indonesia must also further assess the extent to which this policy will affect its commitment to the Paris Agreement.